On the Design of Bouncer: A Robust and Flexible License Management Service for Avoiding Illegal Use of Software - Brasileiro, Francisco Vilar; Bezerra, Tárcio Rodrigues; Cirne Filho, Walfredo Costa; Moura, J. Antão Beltrão (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
The phases of getting a software ready and introducing it into a target-market are seldom emphasised on traditional software engineering process models. Nevertheless, these phases are of the utmost importance in the production process of many commercial applications. Within a mumber of activities carried out on these phases, protection of intellectual property is a key issue that must be tackled. In this paper we present the design of a license management service that can be used to avoid illegal utilisation of applications, specially those executed over a network. The unique architectural model of our license management tool confers on it important characteristics such as robustness and flexibility, not present on other solutions currently available. We compare our approach with others and show that ours is more suitable for a wider range of applications.